Fetal Spinal Anomalies in a First-Trimester Sonographic Screening Program for Aneuploidy - Sepulveda, W (2011)
Objectives: To review the sonographic features of spinal anomalies in first-trimester fetuses presenting for screening for chromosomal abnormalities. Methods: Fetuses with a spinal abnormality diagnosed prenatally or postnatally that underwent first-trimester sonographic evaluation at our institution had their clinical information retrieved and their sonograms reviewed. Results: A total of 21 fetuses complied with the entry criteria including eight with body stalk anomaly, seven with spina bifida, two with Vertebral, Anal, Cardiac, Tracheal, Esophageal, Renal, and Limb (VACTERL) association, and one case each of isolated kyphoscoliosis, tethered cord, iniencephaly, and sacrococcygeal teratoma. One fetus with body stalk anomaly and another with VACTERL association also had a myelomeningocele, making a total of nine cases of spina bifida in our series. Five of the nine (56%) cases with spina bifida, one of the two cases with VACTERL association, and the cases with tethered cord and sacrococcygeal teratoma were undiagnosed in the first trimester. Although increased nuchal translucency was found in seven (33%) cases, chromosomal analysis revealed only one case of aneuploidy in this series. Conclusions: Fetal spinal abnormalities diagnosed in the first trimester are usually severe and frequently associated with other major defects. The diagnosis of small defects is difficult and a second-trimester scan is still necessary to detect most cases of spina bifida. Copyright © 2010 John Wiley & Sons, Ltd.